1978
DOI: 10.1210/endo-103-4-1264
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Calcium in Adrenocorticotropin-Induced Changes in Mitochondrial Pregnenolone Synthesis*

Abstract: The importance of calcium in the ACTH-induced increase in adrenal mitochondrial pregnenolone synthesis was evaluated. In mitochondria prepared in the absence of EDTA and albumin, calcium enhanced the binding of cholesterol to cytochrome P-450 and subsequent pregnenolone synthesis. Although these effects of calcium were slightly greater in control than in ACTH-treated mitochondria, a sizeable effect of ACTH remained even at high calcium levels (500 micron). In mitochondria prepared from adrenals homogenized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In particular, there is evidence that adrenal steroidogenesis is calcium dependent (Farese & Prudente, 1978) and that the aldosterone response to angiotensin II is associated with the intracellular accumulation of calcium (Shima et al, 1979;Fakunding & Cati, 1980). In human studies, however, evidence that calcium antagonists significantly interfere with hormone release is not clearly established.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, there is evidence that adrenal steroidogenesis is calcium dependent (Farese & Prudente, 1978) and that the aldosterone response to angiotensin II is associated with the intracellular accumulation of calcium (Shima et al, 1979;Fakunding & Cati, 1980). In human studies, however, evidence that calcium antagonists significantly interfere with hormone release is not clearly established.…”
Section: Methodsmentioning
confidence: 99%
“…Later hydroxylation reactions, such as that at C-1 lp, may also be stimulated (see Fraser & Lantos, 1978) and this more general effect may be explained by a reported increase in the amounts of adrenodoxin, another component of mixed function oxidase reactions, in some preparations (Asano & Harding, 1976). Most of these effects are accomplished by the stimulation of adenyl cyclase activity and can be mimicked by cyclic AMP or its derivatives (Schulster et al, 1976), and calcium ions play an important role in the response (Simpson & William-Smith, 1975;Farese & Prudente, 1978). Prostaglandins may also be involved in the action of ACTH (Spat, Siklos, Antoni, Nagy & Sziranyi, 1977;Honn & Chavin, 1977).…”
Section: Adrenocorticotrophic Hormonementioning
confidence: 99%
“…Micromolar calcium concentration could stimulate pregnenolone synthesis in rat mitochondria, independently to secretagogues (Farese and Prudente 1978). Extracellular calcium is needed for aldosterone production induced by angiotensin II, K and ACTH (Fakunding, Chow and Catt 1979;Foster et al 1981); calcium entry blocker agents (verapamil and lanthanum) do not inhibit the basal secretion of aldosterone but block the aldosterone output induced by angiotensin II, K and in part by ACTH, the last requiring cyclic AMP as second messenger (Fakunding and Catt 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the importance of calcium on aldosterone secretion (Farese and Prudente 1978 ;Kojima, Lippes, Kojima and Rasmussen 1983;Capponi, Lew, Jomot and Vallotton 1984). Calcium entry blocker agents modulate aldosterone response to angiotensin II, K and to a lesser extent to ACTH (Fakunding, Chow and Catt 1979;Fakunding and Catt 1980;Foster, Lobo, Rasmussen and Marusic 1981).…”
Section: Introductionmentioning
confidence: 98%